Infektifitas berbagai derajat kematangan proglotida cacing pita hymenolepis diminuta (Rudolphi) pada: 1 Kutu beras tribolium castaneum (Herbst) - Elok Budi Retnani; Simon He; Supan Kusumamihardja; Singgih H. Sigit (Hemera Zoa, 1993)
Studies on the effect of the level of maturity of proglottids on the infectivity of Hymenolepis diminuta (Rudilphi) in the intermediate host Tribolium castaneum (Herbst) have been carried out in the Helminthology Laboratory, Faculty of Veterinary Medicine Bogor Agrigultural University.The experiment was carried out using 5 groups of 30 Tribolium castaneumeach which were infected with Hymenolepis diminuta prolottids of different levels of maturity. Each Tribolium group was fed 5% length of the posterior proglotids.The data obtained were analized using analysis of variance continued with Duncan test, where necessary, and analysis of reggression. The number of eggs produced by adult Hymenolepis diminuta originated from all 5 groups of 5% pasterior proglottids were positively correlated with the levels of maturity of the proglottids. The number of cysticercoids produced by the experimental Tribolium were also positively correlated with the maturity levels of the proglottids. In contrast the levels of infectivity, in percentage, of the 5 proglottid groups in the Tribolium were not significantly different from each other indicating that the infectivity of Hynlenolepis diminuta eggs in the Tribolium was not affected by the degree of maturity of the proglottid. From the result of the studies it is concluded that more or less 25% of the posterior proglottids of Hymenolepis diminuta in the rats were gravid.